2014
DOI: 10.1210/jc.2013-3874
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Measured and Calculated Free 25(OH) Vitamin D Levels in Clinical Populations

Abstract: Calculated free 25(OH)D levels varied considerably from direct measurements of free 25(OH)D with discrepancies greatest in the data for African Americans. Differences in DBP binding affinity likely contributed to estimation errors between the races. Directly measured free 25(OH)D concentrations were related to iPTH, but calculated estimates were not. Current algorithms to calculate free 25(OH)D may not be accurate. Further evaluation of directly measured free 25(OH)D levels to determine its role in research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
181
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(198 citation statements)
references
References 28 publications
15
181
1
1
Order By: Relevance
“…Although this limits the generalizability of the results, we did not have sufficient numbers of African-American patients to perform accurate genotype analysis and calculate bioavailable 25(OH)D levels. Calculated free 25(OH)D has been shown to overestimate measured levels, although those calculations did not incorporate VDBP binding affinity by haplotype (35). To the best of our knowledge, we believe that, despite these limitations, this is the first study to report factors that influence VDBP levels in a relatively large cohort of critically ill children and to attempt to address the issue of 25(OH)D bioavailability in critical illness with some rigor.…”
Section: Original Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Although this limits the generalizability of the results, we did not have sufficient numbers of African-American patients to perform accurate genotype analysis and calculate bioavailable 25(OH)D levels. Calculated free 25(OH)D has been shown to overestimate measured levels, although those calculations did not incorporate VDBP binding affinity by haplotype (35). To the best of our knowledge, we believe that, despite these limitations, this is the first study to report factors that influence VDBP levels in a relatively large cohort of critically ill children and to attempt to address the issue of 25(OH)D bioavailability in critical illness with some rigor.…”
Section: Original Researchmentioning
confidence: 96%
“…Bioavailable 25(OH)D can be calculated using several equations and a mathematical model, which incorporate 25(OH)D, VDBP, albumin levels, and VDBP binding affinity by haplotype to varying degrees (32)(33)(34). Recently, an assay of free 25(OH)D has become commercially available, and a comparison of the calculated to measured free 25(OH)D showed that a calculation that does not incorporate VDBP binding affinity overestimates the measured levels (35).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 99%
“…However, in some conditions such parameter may not represent a reliable marker of vitamin D activity due to modifications of free hormone levels independently of total hormone storage and amount [8][9][10]. Consistently with the free hormone hypothesis, only hormone not bound to protein vectors can exert biological actions [11].…”
mentioning
confidence: 88%
“…More than 80 % of circulating vitamin D (i.e., both 25(OH)-vitamin D and 1,25-dihydroxy-vitamin D3) is bound to vitamin D-binding protein (VDBP) which acts as regulator of hormone bio-availability to target tissue [12]. Indeed, VDBP could be either a reservoir of vitamin D prolonging its half-life or a modulator of hormone biological activity [9,10,13]. In clinical conditions, the inhibitory effects of VDBP on vitamin D activity seem to be predominant and some individuals may be misclassified as vitamin D sufficient or insufficient by measurement of serum 25(OH)vitamin D alone in the presence of modifications in VDBP production.…”
mentioning
confidence: 99%
See 1 more Smart Citation